Inspection Program Effectiveness Key Performance Indicator for Pressurized Static Equipment Integrity at Offshore Platform - Haekal, Teuku Ahmad; Soedarsono, Johny Wahyuadi; Munir, Badrul; Sholihin, Muhammad Yudi Masduky (Journal of Materials Exploration and Findings, 2024)
One of the key challenges in asset integrity management system at offshore platform is the lack of visibility regarding performance issues and program effectiveness. Without proper performance measurement systems, it becomes difficult to address positive or negative trends promptly and for management to stay informed about the status and the impact of the inspection program. Therefore, Key Performance Indicator (KPI) is needed to measure inspection program effectiveness to prevent undesirable equipment failures that could lead to Loss of Primary Containment (LOPC) or Process Safety Event (PSE). The developed KPI is the ratio of the number of non-leak inspection findings with a remaining life of less than 3 years to the total number of all anomalies with a remaining life of less than 3 years, including leak findings. By applying this KPI, inspection program effectiveness for an offshore field was monitored and improved firmly from 29% in 2018 to 82% in 2023, with some fluctuations in performance before achieving a strong recovery in later years.